Regression discontinuity designs : theory and applications - Cattaneo, Matias D.; Escanciano, Juan Carlos (Advances in econometrics, 2017)
Volume 38 of Advances in Econometrics collects twelve innovative and thought-provoking contributions to the literature on Regression Discontinuity designs, covering a wide range of methodological and practical topics such as identification, interpretation, implementation, falsification testing, estimation and inference.